Abortion and Selection - Ananat, Elizabeth Oltmans; Gruber, Jonathan; Levine, Phillip B; Staiger, Douglas (The Review of Economics and Statistics, 2009)
Abortion legalization in the early 1970s led to dramatic changes in fertility. Some research has suggested that it altered cohort outcomes, but this literature has been limited and controversial. In this paper, we provide a framework for understanding selection mechanisms and use that framework to both address inconsistent past methodological approaches and provide evidence on the long-run impact on cohort characteristics. Our results indicate that lower-cost abortion brought about by legalization altered young adult outcomes through selection. In particular, it increased likelihood of college graduation, lower rates of welfare use, and lower odds of being a single parent.